The essence and features of the measurement of modern firms in the knowledge economy - S. S. Repin (Путеводитель предпринимателя)
The article considers a knowledge firm whose work is mainly focused on creating new knowledge, expanding the scope of existing knowledge, which today is a rapidly spreading form of economic organization, reflected in the theory of the firm.